Real RGB printing AMOLED with high pixel per inch value. Issue 1 (6th January 2020) - Huo, Si‐Tao; Shao, Li‐Qin; Dong, Ting; Liang, Ji‐Sheng; Bi, Ze‐Tong; He, Mu; Li, Zhe; Gao, Zhuo; Song, Jing‐Yao
Abstract: A 403‐ppi (pixel per inch) real RGB active‐matrix organic light‐emitting diode (AMOLED) was fabricated without using fine metal mask (FMM). Organic light‐emitting materials were printed on array panel, with a novel process that has the advantages of low cost and high pixel density. The uniformity of the organic light‐emitting diodes (OLEDs) was improved with carefully tuning printing parameters, and good panel performance was achieved. The key to such a process was the design of the hexagonal patterning of the pixels. The image quality of the panel with this hexagonal pixel arrangement was evaluated with a bmp format Pixel Layout Simulation picture. Abstract : A 403‐ppi (pixel per inch) real RGB AMOLED panel was successfully fabricated via inkjet printing (IJP) process. One of the key factors was the hexagonal pixel arrangement, and its image quality was evaluated with a bmp format Pixel Layout Simulation picture. Moreover, good uniformity of OLEDs and panel performance was achieved via carefully tuning printing parameters.